2019
DOI: 10.1111/flan.12378
|View full text |Cite
|
Sign up to set email alerts
|

Heritage language education in the United States: A national survey of college‐level Chinese language programs

Abstract: This study reports the results of a national survey of Chinese as a heritage language (CHL) education in U.S. colleges and universities. Conducted during a period of 13 months, the project included an initial survey that elicited general information such as program structure, course offerings, and materials. Of the 619 institutions to which the survey was sent, 246 responses were received, of which 51 institutions were identified as offering CHL courses. A follow‐up survey of heritage‐track instructors at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A heritage speaker (HS) is someone who is “raised in a home where a non‐English language is spoken, who speaks or merely understands the heritage language, and who is to some degree bilingual in English and the heritage language” (Valdés, , p. 1). As noted in Luo, Li, and Li (), programs of study and specific courses within those programs across the K–12 and postsecondary levels have acknowledged HSs’ strengths and needs to different degrees and have supported their language development in differing ways. However, a paradox surrounding the learning and use of Spanish in the United States remains.…”
Section: Introductionmentioning
confidence: 99%
“…A heritage speaker (HS) is someone who is “raised in a home where a non‐English language is spoken, who speaks or merely understands the heritage language, and who is to some degree bilingual in English and the heritage language” (Valdés, , p. 1). As noted in Luo, Li, and Li (), programs of study and specific courses within those programs across the K–12 and postsecondary levels have acknowledged HSs’ strengths and needs to different degrees and have supported their language development in differing ways. However, a paradox surrounding the learning and use of Spanish in the United States remains.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized learning has also been considered key for success (Luo, Li, & Li, 2019). In their study of a Chinese heritage program, they found that students worked better and faster using learner-centered online materials and engaging in multimedia projects.…”
Section: Challenges For Proficiency Assessmentmentioning
confidence: 99%